A Cluster-Based Vehicular Ad-hoc Network Handoff Scheme Inspired by Ant Colony Optimization - Roy, P; Santra, P; Hazra, D; Mahata, P (International Journal of Computer Sciences and Engineering, 2025)
In recent times, the drivers and passengers of vehicles are not confined to only travelling in their vehicles. They are feeling the need for enhanced services on the go. As a result, the time has come when it is necessary to bring about improvements in the current Intelligent Transport System (ITS). Handoff in VANET is one of the common areas that require attention of researchers. During the Handoff process, it is necessary to ensure that the vehicle maintains continuous connection with the network. This will decrease the amount of packet loss thus ensuring Quality of Service (QoS). In this paper we have proposed a novel scheme; Cluster Based Vehicular Handoff (CBVH) for reducing load on a single backbone device using the concept of clustering. The scheme also reduces packet loss during handoff by proactively caching packets intended for the node that is participating in the handoff process.